Development of Diagnostic Capabilities for Complications of Bacterial Infection in Diabetic Patients (The Review of Diabetic Studies, 2022)
OBJECTIVE: Our objective was to assess the pattern of urine infections, the most common pathogen, and their susceptibility pattern to antibiotics among Saudi diabetic patients. METHODS: We performed a year-long cross-sectional study from January 2018 to January 2019 at KAAU Hospital in Riyadh, KSA. We cultured the urine specimens obtained from diabetic patients based on optimal aerobic and anaerobic microbiological methods. By adopting standard microbiological methods, we identified the bacterial isolates. We also followed the guidelines of the Clinical and Laboratory Standards Institute (CLSI) to do antibiotic susceptibility testing. RESULTS: A total of 100 isolates were evaluated, and a total of 22 organisms were isolated. The majority were multidrug-resistant organisms. Streptococcus haemolyticus was the most frequent organism and rated (15%). It was followed by Staphylococcus hominis (11%), Pseudomonas aeruginosa (9%), Enterococcus faecalis (9%), Enterococcus fiseum (7%), Escherichia coli (7%), Staphylococcus aureus (7%), Staphylococcus lantus (5%) and Klebsiella pneumoniae (5%). We also found multi-microbial infections. Most of the organisms were susceptible to tigecycline, gentamycin, and nitrofurantoin, rating (88%), (84%) and (78%), respectively. CONCLUSIONS: Our study revealed that a wide range of pathogens affects the diabetes patients. Staphylococcus haemolyticus is the most prevalent pathogen. We observed considerable antimicrobial resistance. Tigecycline had a wide sensitivity spectrum and was effective against most of the bacteria. Thus, it can be used as an empirical antibiotic.